APPLICATION OF THE INTERNET OF THINGS IN PHARMACEUTICAL INDUSTRY SUPPLY CHAINS - N. Yu. Barkova; D. D. Zherega; E. A. Popova; V. P. Logacheva (Вестник университета)
Сurrent temperature monitoring, humidity, physical condition and real-time data transmission are extremely important in the pharmaceutical supply chains. The intelligent logistics system for monitoring the state of objects, implemented on the basis of the Internet of things, which can be used for the pharmaceutical industry, has been considered in this article. The two-level network architecture of the IOT platform has been reviewed. The first level is radio frequency object identification, and the second level is organization of wireless sensor network. By adapting the proposed system, the pharmaceutical company can easily monitor and control the quality of the goods during transportation.